Slow uniform electrical activation during sinus rhythm is an indicator of reentrant VT isthmus location and orientation in an experimental model of myocardial infarction. (November 2020) - Ciaccio, Edward J.; Coromilas, James; Wan, Elaine Y.; Yarmohammadi, Hirad; Saluja, Deepak S.; Biviano, Angelo B.; Wit, Andrew L.; Peters, Nicholas S.; Garan, Hasan
Highlights: Computerized means are used to analyze the electrical activation of the heart. Activation maps are constructed by automarking electrograms by computer. Computer regression analysis is implemented to analyze conduction properties. Based on the results, these methods could be helpful for catheter ablation of VT. Abstract: Background: To validate the predictability of reentrant circuit isthmus locations without ventricular tachycardia (VT) induction during high-definition mapping, we used computer methods to analyse sinus rhythm activation in experiments where isthmus location was subsequently verified by mapping reentrant VT circuits. Method: In 21 experiments using a canine postinfarction model, bipolar electrograms were obtained from 196-312 recordings with 4mm spacing in the epicardial border zone during sinus rhythm and during VT. From computerized electrical activation maps of the reentrant circuit, areas of conduction block were determined and the isthmus was localized. A linear regression was computed at three different locations about the reentry isthmus using sinus rhythm electrogram activation data. From the regression analysis, the uniformity, a measure of the constancy at which the wavefront propagates, and the activation gradient, a measure that may approximate wavefront speed, were computed. The purpose was to test the hypothesis that the isthmus locates in a region of slow uniform activation bounded by areas of electrical discontinuity. Results: Based on the regression parameters, sinus rhythm activation along the isthmus near its exit proceeded uniformly (mean r 2 = 0.95±0.05) and with a low magnitude gradient (mean 0.37±0.10mm/ms). Perpendicular to the isthmus long-axis across its boundaries, the activation wavefront propagated much less uniformly (mean r 2 = 0.76±0.24) although of similar gradient (mean 0.38±0.23mm/ms). In the opposite direction from the exit, at the isthmus entrance, there was also less uniformity (mean r 2 = 0.80±0.22) but a larger magnitude gradient (mean 0.50±0.25mm/ms). A theoretical ablation line drawn perpendicular to the last sinus rhythm activation site along the isthmus long-axis was predicted to prevent VT reinduction. Anatomical conduction block occurred in 7/21 experiments, but comprised only small portions of the isthmus lateral boundaries; thus detection of sinus rhythm conduction block alone was insufficient to entirely define the VT isthmus. Conclusions: Uniform activation with a low magnitude gradient during sinus rhythm is present at the VT isthmus exit location but there is less uniformity across the isthmus lateral boundaries and at isthmus entrance locations. These factors may be useful to verify any proposed VT isthmus location, reducing the need for VT induction to ablate the isthmus. Measured computerized values similar to those determined herein could therefore be assistive to sharpen specificity when applying sinus rhythm mapping to localize EP catheter ablation sites.